2001
DOI: 10.1111/j.1651-2227.2001.tb00439.x
|View full text |Cite
|
Sign up to set email alerts
|

Current diagnosis, management and morbidity in paediatric inflammatory bowel disease

Abstract: In the 1970s several reports highlighted the long delay in diagnosis often experienced by children with Crohn's disease. In recent years this disorder has attracted much publicity, and many believe that the incidence has increased substantially. The aim of this investigation was to determine whether heightened awareness had shortened the interval to diagnosis, improved clinical management and reduced morbidity. A retrospective study was therefore carried out on 112 children with inflammatory bowel disease (64 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 19 publications
1
18
3
Order By: Relevance
“…This result was similar to that of Sawczenko and Sandhu [4], who showed that only 25% of CS patients presented with the 'classic triad' and 72% with abdominal pain. In contrast to our results and those of Sawczenko and Sandhu [4], Spray et al [21] reported that most CD children presented with the classical triad. Most children with UC presented with hematochezia and diarrhea in our study; this was similar to what was seen in Western studies [4,5,21].…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…This result was similar to that of Sawczenko and Sandhu [4], who showed that only 25% of CS patients presented with the 'classic triad' and 72% with abdominal pain. In contrast to our results and those of Sawczenko and Sandhu [4], Spray et al [21] reported that most CD children presented with the classical triad. Most children with UC presented with hematochezia and diarrhea in our study; this was similar to what was seen in Western studies [4,5,21].…”
Section: Discussioncontrasting
confidence: 56%
“…With UC patients, our study showed a female predominance, but the Korean adult report found no gender bias [14]. In contrast to what was seen in the Korean work, Western studies have shown no gender differences in either adults or children [4,5,21,25,26]. Further study will be required, because our patient number was small.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Often children present IBD-like phenotypes and symptoms; however, they do not suffer from IBD. A long period of unmanaged symptoms can significantly impact on growth; thus, early treatments are essential to preserve the long-term quality of life of patients (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Delay in diagnosing IBD, and the resultant delay in receipt of appropriate treatment, may prolong suffering and can lead to complications such as anemia, irreversible growth failure, and delayed sexual maturation. 4,5 According to guidelines, primary care physicians should refer children with chronic diarrhea, recurrent abdominal pain, or both for specialist care if red flags are present. 6,7 The red flags are nonspecific and discriminate poorly between functional and organic gastrointestinal diseases, [8][9][10] often leading to referral and extensive diagnostic testing.…”
Section: Introductionmentioning
confidence: 99%